Convention on Civil Liability for Damage Resulting from Activities Dangerous to the Environment - Arsić, Zoran (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
The Convention aims at ensuring adequate compensation for damage resulting from activities dangerous to the environment and also provides for means of prevention and reinstatement. It considers that the problems of adequate compensation for emissions released in one country causing damage in another country are also of an international nature. The system of the Convention is based on objective liability taking into account the "polluter pays" principle. However, specific rules are provided concerning the fault of the victim, causation, joint liability of the operators of installations or sites for damage, and a compulsory financial security scheme to cover liability under the Convention.